Clostridium Perfpringens and Sulphite Reducing Clostridia Densities in Selected Tropical Malaysian Rivers - Lee, F.C.H.; Hakim, S.L.; Kamaluddin, M.A.; Thong, Kwai Lin (SEAMEO Regional Tropical Medicine and Public Health Network, 2012)
Clostridium perfringens (CP) and sulphite reducing clostridia (SRC) densities in the Selangor River, Bernam River and Tengi River Canal were examined between April 2007 and January 2008. Water samples were taken from two or three locations along each river, using either depth-integration or grab sampling methods. The downstream sampling site of the Selangor River, Rantau Panjang, reported the highest arithmetic mean of CP and SRC densities (583.45 and 8,120.08 cfu/100 ml, respectively). Both CP and SRC densities in the Selangor River increased further downstream, but the reverse was true in the Bernam River. The SRC densities in these rivers were significantly different from each other (p<0.05) when comparing upstream and downstream results, but CP densities were not significantly different (p>0.05). SRC densities were significantly correlated (p<0.05) in different locations along the Selangor River and the Bernam River. The CP densities did not show such pattern (p>0.05). River discharge had no significant correlation with SRC or CP densities by study site (p>0.05). Since the Selangor River has a denser human population along its banks, this study confirms CP as a suitable indicator of human fecal contamination. However, tracing CF distribution along the river is more difficult than SRC. To our knowledge, this is the first study of CP and SRC densities from Malaysian rivers. CP densities found in this study were within the range of general water bodies reported from other countries.